Strategi Pelayanan Administrasi Kependudukan Dinas Kependudukan Dan Pencatatan Sipil kota Bandung Dalam Mencegah Penyebaran Virus Covid-19 - aja, Ahtuduriat (Prodi Administrasi Publik FISIP UNPAS, 2021)
Abstract Service strategy is how someone responds to a situation within the organization by providing solutions or finding a way to get out of the situation. The service strategy carried out by the Department of Population and Civil Registration of the City of Bandung is a form of innovation so that the services provided are more effective and efficient.Coupled with the lack of facilities at the Office of Population and Civil Registration of the City of Bandung, administrative service outlets are provided outside the official offices, this action is one of the innovations and service strategies that have been carried out by the Bandung City Office of Population and Civil Registration.Until now, the service strategy is one of the efforts made by the Bandung City Population and Civil Registration Office to improve the quality of good service so that services become more effective and efficient. Keywords: Service Strategy, Innovation